Emprego de líquidos iônicos a base de Cloreto de colina (Deep Eutectic Solvent) no processo de lavagem do biodiesel de soja - Santos, Matheus Romeiro Manoel dos (2019)
Biodiesel is a biofuel of great importance for the diversification of the world energy matrix and reducing dependence on fuels of non-renewable origin that degraded the environment and endangers human life. The production of this biofuel from transesterification requires long and onerous steps, wasting large volumes of water to remove impurities in order to meet regulatory parameters. The aims are to develop and characterize an ionic liquid of the DES (Deep Eutectic Solvent) type, choline chloride (HBA) base, capable of removing impurities from soybean biodiesel. Thirteen ionic liquids were evaluated, mixing HBD's glycerol, ethylene glycol and triethyleneglycol, in different proportions of biodiesel, selecting for later tests the mixed option with highest removal efficiency. The ionic liquid composed of choline chloride (HBA), glycerol and triethyleneglycol (HBDs) (1:2:1), mixed with biodiesel in a molar ratio of 1:1, was the most efficient, increasing the content of esters (98,5%) and reducing the acylglycerols and glycerol, below the limits determined by the ANP. The ionic liquid was able to solubilize the water, methanol and catalyst molecules, but did not reduce the required levels. Agitation time influences the increase of ester content, and the best extraction of impurity molecules are in 60 minutes of mixing. The temperature increase did not show an influence on biodiesel washing, and formation of hydrogen bonds is the main force of the purification. The reuse of the ionic liquid was possible once only, and its use is inefficient for new washes. The density, viscosity and pH of the ionic liquid developed are, respectively, 1,17 g.cm-3, 112,8 cP and 5,4. The thermal analysis determined the crystallization temperature of the ionic liquid is -17.98 ºC, and the decomposition and final decomposition temperatures are 146,8 ºC and 359,3 ºC, respectively. Washing soybean biodiesel with the developed ionic liquid has great potential as a substitute for conventional wet-washing techniques, as it is efficient and represents an 83% of water saving consumption per liter of washed biodiesel.